Honey solution as a natural biostimulant for the growth of capsicum annuum L. - Mohamad Mahbob, Emi Norzehan; Shahrim, Mohammad Afiq; Alias, Nurulfitri; Mohammad Nor, Nur Aireen; Izwani Saini, Lily Shafinaz; Zuhar, Nur Amalina; Mohd Saleh, Nabila Huda (2025)
Honey is a natural product rich in sugars, amino acids, vitamins, and bioactive compounds, with potential applications as a sustainable plant biostimulant. This study evaluated the effects of different concentrations of honey solution on the growth of Capsicum annuum by measuring plant height over a five-week period. Five treatments were prepared: fertilizer only (control), and honey solutions at concentrations of 5%, 10%, 15%, and 20% (v/v) without fertilizer. Each treatment was replicated four times, and solutions were applied fortnightly at weeks 1, 3, and 5. Plant height was recorded weekly, and mean values were compared across treatments. The results showed that the 20% honey solution produced the greatest increase in average plant height (11.33±1.15 cm), whereas the 5% solution resulted in the lowest growth (1.63±0.48 cm). The control achieved 6.75±0.96 cm, which was slightly higher than the 10% (6.00±0.82 cm) and 15% (6.50±1.29 cm) treatments. These findings indicate that honey supplementation influenced growth in a concentration-dependent manner, with only the higher concentration producing substantial improvement compared to fertilizer alone. The stimulatory effects of honey are likely linked to its nutrient content and bioactive compounds, which may enhance microbial activity, nutrient uptake, and plant metabolic processes. In conclusion, honey solution particularly at 20% concentration demonstrated potential as an eco-friendly biostimulant for enhancing the growth of C. annuum. Future research should investigate additional growth parameters, such as leaf development, biomass accumulation, and fruit yield, and extend testing to other crops and environmental conditions. These findings support the potential of honey as a sustainable alternative to synthetic fertilizers in horticultural production.